The Mouse Aire Gene: Comparative Genomic Sequencing, Gene Organization, and Expression - Blechschmidt, Karin; Schweiger, Michal; Wertz, Karin; Poulson, Richard; Christensen, Hoang-My; Rosenthal, Andre; Lehrach, Hans; Yaspo, Marie-Laure

(untitled) (Genome Research, 1999)
Mutations in the human AIRE gene (hAIRE) result in the development of an autoimmune disease named APECED (autoimmunepolyendocrinopathycandidiasis ectodermaldystrophy; OMIM 240300). Previously, we have cloned hAIRE and shown that it codes for a putative transcription-associated factor. Here we report the cloning and characterization of Aire, the murine ortholog of hAIRE. Comparative genomic sequencing revealed that the structure of the AIRE gene is highly conserved between human and mouse. The conceptual proteins share 73% homology and feature the same typical functional domains in both species. RT–PCR analysis detected three splice variant isoforms in various mouse tissues, and interestingly one isoform was conserved in human, suggesting potential biological relevance of this product. In situ hybridization on mouse and human histological sections showed that AIRE expression pattern was mainly restricted to a few cells in the thymus, calling for a tissue-specific function of the gene product.